Pengukuran Kadar Ekstraktif dan Sifat Warna pada Kayu Teras Jati Doreng (Tectona grandis) - Ganis Lukmandaru (Jurnal Ilmu Kehutanan, 2009)
Measurement of Extractive Content and Color properties on Black-streaked Heartwood of Teak (Tectona grandis)Teak (Tectona grandis L.f) in certain areas of Java usually has black streaked heartwood or has been known as "doreng". In general, the color of wood is related to the kinds and amounts of extractives, therefore, black streak that appeared on the heartwood was studied by means of color measurements and the determination of extractive content. The study was made with 13 trees of black streaked heartwood and 5 trees of normal heartwood. The wood powder (40-60 mesh) was extracted successively with ethanol-benzene (1:2, v/v) for 8 h and hot water for 3 h. The used system of color measurements was CIEL*a*b* which represents brightness, redness and yellowness. The discolored wood was contained substantially more ethanol-benzene soluble extractive content (12 - 22%) than did the normal heartwood (7 - 11%). The yield differences of hot-water soluble extracts were not as pronounced. Beside the brightness (L*), the differences in redness (a*) and yellowness (b*) between the normal (L* = 51-61, a* = 4 to 7, b* = 24 to 28) and black streaked heartwood (L* = 42-51, a* = 6 to 9, b* = 20 to 25) before the extraction, were notable. The total color differences ( E*) before and after extractions, however, were not significantly differed between the discolored ( E* = 6 to 13) and normal heartwood ( E* = 5 to 11) parts. Correlation analysis revealed strong correlations between ethanol-benzene soluble extractive content with L* (r = -0.97) and b* (r = -0.94). The hot-water soluble extract was moderately correlated with a* (r = 0.54) and the difference in redness ( a*) before and after extractions (r = 0.75).